2017
DOI: 10.3389/fpls.2017.01911
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormone and Light Regulation of Chlorophyll Degradation

Abstract: Degreening, due to the net loss of chlorophyll (Chl), is the most prominent symptom during the processes of leaf senescence, fruit ripening, and seed maturation. Over the last decade or so, extensive identifications of Chl catabolic genes (CCGs) have led to the revelation of the biochemical pathway of Chl degradation. As such, exploration of the regulatory mechanism of the degreening process is greatly facilitated. During the past few years, substantial progress has been made in elucidating the regulation of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 92 publications
1
36
0
Order By: Relevance
“…Water deficits are known to induce genes associated with chlorophyll degradation and metabolite recycling (Zhu et al 2017), and these processes eventually lead to cell death. Thus it was not surprising we found large transcript decreases for genes associated with chlorophyll reduction, such as decreased transcript levels for several highly expressed light-harvesting chlorophyll a/b-binding (LHCB) proteins like Cc04_g16410 (FC = −5.52) and a gene encoding a putative magnesium-chelatase subunit H protein (Cc06_g17100, FC = −4.15).…”
Section: Discussionmentioning
confidence: 99%
“…Water deficits are known to induce genes associated with chlorophyll degradation and metabolite recycling (Zhu et al 2017), and these processes eventually lead to cell death. Thus it was not surprising we found large transcript decreases for genes associated with chlorophyll reduction, such as decreased transcript levels for several highly expressed light-harvesting chlorophyll a/b-binding (LHCB) proteins like Cc04_g16410 (FC = −5.52) and a gene encoding a putative magnesium-chelatase subunit H protein (Cc06_g17100, FC = −4.15).…”
Section: Discussionmentioning
confidence: 99%
“…During the fruit ripening, the fruit peel color of some varieties turns from green to yellow, a process called degreening. This is virtually a process of chlorophyll degradation mediated by Chl catabolic genes (CCGs) [41]. Hongyu is a typical variety whose fruits experience degreening process and exhibit yellow-peel, while Guire82 is a Chinese cultivar derived from yellow-peel Neelum and represents atypical stay-green peel (Fig.…”
Section: Mango Fruit Peel Pigmentationmentioning
confidence: 99%
“…Genes involved in the photosynthesis and sugar metabolism are retrieved based on the information provided in Plant Metabolic Network [105] (https://www.plantcyc.org). Polyphenol metabolism and chlorophyll metabolism genes were retrieved based on references [41,106]. Carotenoid biosynthesis genes were retrieved from AtIPD [107].…”
Section: Manual Revision For Certain Genes and Gene Familiesmentioning
confidence: 99%
“…Rosemary and lemongrass extracts at the concentration of 20% acted negatively, since there was a chlorophyll a reduction. Some studies have shown that the methyl jasmonate molecule acts in the process of plant senescence, promoting chlorophyll degradation Zhu et al (2017). In this way, the methyl jasmonate present in rosemary leaves may have contributed to the reduction of chlorophyll a when compared to the control.…”
Section: Resultsmentioning
confidence: 99%